More than skin deep: dissecting Donne’s imagery of humours - Bumke, Alison (Oxford University Press, 2015)
This article explores John Donne’s imagery of humoral complexions in verse letters to patrons and in sermons. In the early modern period, the term ‘complexion’ referred to a person’s unique mixture of humours, the four bodily fluids thought to determine appearance, behaviour, and health. Donne refers to complexions to raise questions of moral responsibility. Whether he seeks a patron’s support or a congregation’s repentance, he reworks humoral theories in elaborate, often playful ways, illustrating the necessity of whichever action he recommends. This article argues that his imagery of complexions warrants close attention, both for its rhetorical innovations and for what it reveals about Donne’s verse letters. By focusing on his complexions trope, we can look past letters’ flattery and recognize the literary trademarks - the imaginative thinking, wordplay, and themes - of Donne’s other texts, and of his sermons, in particular.